Lability of Cd, Cr, Cu, Mn and Pb complexed by aquatic humic substances - de Castro, Gustavo Rocha; Padilha, Cilene do Carmo Federici; Rocha, Júlio Cesar; Valente, José Pedro Serra; Florentino, Ariovaldo de Oliveira; Padilha, Pedro Magalhães (Eclética Química, 2005)
The lability of Cd(II), Cr(III), Cu(II), Mn(II) and Pb(II) complexed by humic substances (HSs) was investigated by means of ion exchange on cellulose modified with p-aminobenzoic groups (Cell-PAB), using a batch procedure. The HSs were extracted from water samples using adsorption in a column packed with XAD 8 resin. The metal-HS complexes were prepared by adding solutions containing all the aforementioned metal ions ( Cd(II), Cr(III), Cu(II), Mn(II) and Pb(II) ). The results indicated that the distribution coefficients (Kd) of Cell-PAB decreased with the presence of HSs, and that the lability of metal fractions complexed by HSs decreases in pH values > 4.0, complexation time > 10 h and HS concentration > 500 mg L -1 . The metal exchange between HSs and Cell-PAB exhibited the following order of metal ion lability: Cd < Pb < Mn ≅ Cr < Cu.